Findings of the joint dark energy mission figure of merit science working group - Albrecht, Andreas; Amendola, Luca (Arxiv, 2009)
These are the findings of the Joint Dark Energy Mission (JDEM) Figure of Merit (FoM) Science Working Group (SWG), the FoMSWG. JDEM is a space mission planned by NASA and the DOE for launch in the 2016 time frame. The primary mission is to explore the nature of dark energy. In planning such a mission, it is necessary to have some idea of knowledge of dark energy in 2016, and a way to quantify the performance of the mission. In this paper we discuss these issues.